Family-based treatment for pediatric eating disorders: evidence and guidance for delivering integrated interdisciplinary care. Issue 1 (2nd January 2023) - Forsberg, Sarah; Gorrell, Sasha; Accurso, Erin C.; Trainor, Claire; Garber, Andrea; Buckelew, Sara; Le Grange, Daniel
ABSTRACT: Eating disorders (EDs) are complex psychiatric diagnoses requiring specialized care. Family-based treatment (FBT) is the first-line treatment for adolescent anorexia nervosa and is also efficacious for other EDs. This study describes practice changes due to the implementation of an integrated interdisciplinary FBT-aligned treatment program for EDs at a large tertiary care hospital in the United States. We examined the feasibility and acceptability of implementation, barriers to implementation, and impact on providers' roles over a one-year period. Practice changes came with shifts in roles and were largely experienced as acceptable with good suitability. Barriers identified may inform future interdisciplinary implementation efforts.